Satellite accretion in action: a tidally disrupting dwarf spheroidal around the nearby spiral galaxy NGC 253 - Romanowsky, Aaron J.; Martínez-Delgado, David; Morales, Gustavo; Grebel, Eva K. (Arxiv, 2015)
We report the discovery of NGC 253-dw2, a dwarf spheroidal (dSph) galaxy candidate undergoing tidal disruption around a nearby spiral galaxy, NGC 253 in the Sculptor group: the first such event identified beyond the Local Group. The dwarf was found using small-aperture amateur telescopes, and followed up with Suprime-Cam on the 8 m Subaru Telescope in order to resolve its brightest stars. Using g- and R_c-band photometry, we detect a red giant branch consistent with an old, metal-poor stellar population at a distance of ~ 3.5 Mpc. From the distribution of likely member stars, we infer a highly elongated shape with a semi-major axis half-light radius of (2 +/- 0.4) kpc. Star counts also yield a luminosity estimate of ~ 2x10^6 L_Sun,V (M_V ~ -10.7). The morphological properties of NGC 253-dw2 mark it as distinct from normal dSphs and imply ongoing disruption at a projected distance of ~ 50 kpc from the main galaxy. Our observations support the hierarchical paradigm wherein massive galaxies continously accrete less massive ones, and provide a new case study for dSph infall and dissolution dynamics. We also note the continued efficacy of small telescopes for making big discoveries.